Effect of dietary protein sources on production performance, egg quality, and plasma parameters of laying hens - Wang, Xiaocui (Asian-Australas J Anim Sci, 2017)
OBJECTIVE: This study was conducted to evaluate the effects of dietary protein sources (soybean meal, SBM; low-gossypol cottonseed meal, LCSM; double-zero rapeseed meal, DRM) on laying performance, egg quality, and plasma parameters of laying hens. METHODS: A total of 432 32-wk-old laying hens were randomly divided into 6 treatments with 6 replicates of 12 birds each. The birds were fed diets containing SBM, LCSM(100), or DRM(100) individually or in combination with an equal amount of crude protein (CP) (LCSM(50), DRM(50), and LCSM(50)-DRM(50)). The experimental diets, which were isocaloric (metabolizable energy, 11.11 MJ/kg) and isonitrogenous (CP, 16.5%), had similar digestible amino acid profile. The feeding trial lasted 12 weeks. RESULTS: The daily egg mass was decreased in the LCSM(100) and LCSM(50)-DRM(50) groups (p<0.05) in weeks 41 to 44. The LCSM(50) group did not affect egg production compared to the SBM group in weeks 41 to 44 (p>0.05) and showed increased yolk color at the end of the trial (p<0.05). Compared to the SBM group, the LCSM(100) and LCSM(50)-DRM(50) groups showed decreased albumen weight (p<0.05), CP weight in the albumen (p<0.05) and CP weight in the whole egg (p<0.05) at 44 weeks. Plasma total protein (TP) levels were lower in the LCSM(100) group than in the SBM group at 44 weeks (p<0.05); however, TP, albumin, and globulin levels were not significantly different between the LCSM(50) group and the SBM group or between the DRM(50) group and the SBM group (p>0.05). CONCLUSION: Together, our results suggest that the LCSM(100) or DRM(100) diets may produce the adverse effects on laying performance and egg quality after feeding for 8 more weeks. The 100.0 g/kg LCSM diet or the148.7 g/kg DRM diet has no adverse effects on laying performance and egg quality.